A comparison of three platelet function tests in ischemic stroke patients with antiplatelet therapy. (August 2020) - Shao, Tengfei; Cheng, Yue; Jin, Jiali; Huang, Lili; Yang, Dan; Luo, Caimei; Han, Zhou; Wang, Zhongyuan; Ge, Weihong; Xu, Yun
Highlights: Antiplatelet drugs resistance is a risk factor of recurrence of ischemic stroke. We tested three platelet function assays and CYP2C19 genotype. LTA, TEG and PFA-200 all did well to evaluate aspirin effect. TEG was not quite suitable for clopidogrel. Abstract: Predicting the effectiveness of antiplatelet drugs is critical to precision antiplatelet therapy. However, there is a lack of an acceptable method, although there are a variety of methods for detecting platelet function. In this study, we compared three major platelet function tests to assess their performance and found better methods for platelet function evaluation after aspirin or clopidogrel treatment in ischemic stroke patients by comparative study. A total of 249 ischemic stroke patients were enrolled who were treated with aspirin or clopidogrel or both. Three platelet function tests including light transmittance aggregometry (LTA), thromboelastography (TEG), platelet function analyzer (PFA) were performed as well as CYP2C19 genotype determination. Correlation analyses and kappa statistics were used. All three methods were effective in evaluating aspirin function. However, only LTA and TEG had good correlation and consistency ( r  = -0.37, kappa = 0.634). TEG-ADP was the least sensitive for clopidogrel, as the platelet inhibition ratio did not differ between the clopidogrel-user group and the control ( P  = 0.074), while LTA and PFA were sensitive ( P ＜ 0.001). Correlations between platelet assays were poor for clopidogrel (the absolute value of r range from 0.13 to 0.35) and so was the agreement (Kappa from 0.232 to 0.314). LTA and PFA have a good correlation with CYP2C19 genotyping ( P  = 0.034 and 0.014). In conclusion, all three tests were able to evaluate aspirin effect, LTA-AA and TEG-AA had a good correlation. TEG perform badly for clopidogrel effect detection. The fair-to-modest agreement among assays indicated further study was indispensable.